Design of Wideband Radome for Antenna Array for Digital TV Broadcasting - เด่นตรี, สิทธิชัย; เหลือแดง, บัญชา (RMUTL Engineering Journal, 2018)
Considerations of electromagnetic properties for radome design of wideband applications of digital TV antenna array for broadcasting. Geometrically-designed materials are appropriately chosen for optimal wave propagation performance. The radome design guidelines for wideband digital television broadcasting was presented. Radiated power is spread over 90% throughout the frequency range 510 to 790 MHz and the antenna gain when the radome is equal to 8.741 to 11.65 dBi. The information presented is important for digital television antennas to be developed in the future